The Fourth Evaluation Report on Working of Community Protects and N. E. S. Blocks Vol. I April 1957 - Planning Commission (Planning Commission, 1957)
The Programme Evaluation Organisation is now in the fifth year of its operation, and this is the fourth Report that it is issuing. Meanwhile, there has been a rapid expansion of the Community Development and National Extension Service programmes in the country. These now cover nearly 200,000 villages, and are expected to cover the entire country by 1960-61. With this, the work of the Programme Evaluation Organisation is bound to increase and also its responsibility. To enable it to cope with this increased work and responsibility, the Planning Commission have re-organised the Programme Evaluation Organisation and created a Programme Evaluation Board under the direction of which they have now placed the Programme Evaluation Organisation.
Programme Evaluation Organisation Planning Commission